2021
DOI: 10.1186/s12978-021-01119-6
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive health interventions for Inuit youth in the north: a scoping review

Abstract: Background Inuit have thrived in the northern regions of Canada and Alaska for thousands of years. Recent evidence suggests that Inuit in this region have experienced systemic barriers to reproductive health with resulting disparities in reproductive health-related outcomes including those among youth. Northern youth-focused reproductive health intervention research or evaluations have not to date been well summarized. The objective of this scoping review was to summarize the literature over th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
(58 reference statements)
0
2
0
1
Order By: Relevance
“…While Canadian prenatal care is "universally" available, previous studies have shown that both newcomer and Indigenous Canadians (i.e., people from two populations likely to be racialized) are less likely to engage in full courses of prenatal care, for reasons relating to linguistic accessibility, cultural safety, and geographic remoteness. [35][36][37] Although we did not measure experiences of discrimination and thus cannot assess whether such experiences complicate racialized Canadians' access to prenatal care, our data clearly shows that racialization status is associated with worse pregnancy health experiences. This is consistent with data indicating that immigrants to Canada who are likely to be racialized perceive such racializing discrimination as a barrier to prenatal care experiences.…”
Section: Discussionmentioning
confidence: 78%
“…While Canadian prenatal care is "universally" available, previous studies have shown that both newcomer and Indigenous Canadians (i.e., people from two populations likely to be racialized) are less likely to engage in full courses of prenatal care, for reasons relating to linguistic accessibility, cultural safety, and geographic remoteness. [35][36][37] Although we did not measure experiences of discrimination and thus cannot assess whether such experiences complicate racialized Canadians' access to prenatal care, our data clearly shows that racialization status is associated with worse pregnancy health experiences. This is consistent with data indicating that immigrants to Canada who are likely to be racialized perceive such racializing discrimination as a barrier to prenatal care experiences.…”
Section: Discussionmentioning
confidence: 78%
“…Program pendidikan khusus remaja, pendekatan penelitian partisipatif, dan pendirian pusat bersalin dan layanan kebidanan terbukti menjanjikan dalam meningkatkan kesehatan reproduksi di kalangan remaja Inuit (Mikhail et al, 2021). Demikian pula, intervensi berbasis bukti memainkan peran penting dalam meningkatkan kesehatan seksual dan reproduksi remaja di negaranegara berpenghasilan rendah dan menengah, dengan menekankan pentingnya dampak berkelanjutan dan hasil yang adil (Salam et al, 2016).…”
Section: Promosi Kesehatan Reproduksiunclassified
“…Available literature demonstrates that Inuit youth experience considerably worse sexual health outcomes than other Canadian youth. For example, transmission rates have been reported to be over 10 times the national average for chlamydia, gonorrhea, and syphilis among Inuit youth and teenage pregnancy is over 5 times the national average (Corosky & Blystad, 2016; Mikhail et al, 2021). For Métis youth, there is a significant gap in the literature surrounding sexual health.…”
Section: Limitationsmentioning
confidence: 99%